DIACEREIN AS THE DRUG OF CHOICE IN THE THERAPY OF KNEE OSTEOARTHRITIS WITH SECONDARY RECURRENT SYNOVITIS - M. I. Udovika (Научно-практическая ревматология, 2016)
Objective: to evaluate the efficacy and tolerability of diacerein in the therapy of primary knee osteoarthritis (OA) with secondary recurrent synovitis.Subjects and methods. The 3-month open-label randomized controlled trial enrolled 133 patients with OA. Group 1 consisted of 68 subjects (42 women and 26 men; mean age 54.22±4.29 years) who took diacerein 100 mg/day for 3 months. Group 2 (a control group) included 65 subjects (45 women and 20 men; mean age 53.50±3.27 years) who received chondroitin sulfate 1000 mg/day + glucosamine sulfate 1000 mg/day and meloxicam 7.5 mg/day for 3 months too.Results and discussion. After a therapy cycle, Group 1 patients displayed a statistically significant decrease in the Lequesne index from 13.92±2.16 to 5.95±0.92 (p=0.00005); in Group 2, this index significantly reduced from 16.72±1.78 to 10.76±1.54 (p=0.001). Pain intensity on the visual analogue scale decreased significantly from 70.88±7.06 to 22.05±6.36 mm (p<0.00001) in Group 1 and from 72.46±7.02 to 39.84±6.67 mm (p<0.0004) in Group 2. A persistent analgesic effect was achieved at weeks 6 and 7 in Groups 1 and 2, respectively. The therapeutic effect was estimated as very good and good by 48 and 52% of the patients, respectively, in Group 1 and as good and moderate by 43 and 57% in Group 2. Three months after a therapy cycle effusion in the affected knee substantially increased (from 21.70±6.29 to 29.16±3.63 ml; p<0.001) in Group 2 and slightly increased (from 5.86±3.10 to 6.12±1.09 ml; p>0.05) in Group 1, which confirms the steady-state effect of diacerein. The results of the performed open-label randomized clinical trial showed marked analgesic and anti-inflammatory effect of diacerein and allow to recommend it as the drug of choice to treat knee OA with secondary recurrent synovitis.